2021
DOI: 10.1007/s11920-021-01233-z
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Behavior and Psychiatric Inpatients: a Narrative Review of the Literature with a Focus on the European Experience

Abstract: Purpose of Review We summarized peer-reviewed literature on aggressive episodes perpetrated by adult patients admitted to general hospital units, especially psychiatry or emergency services. We examined the main factors associated with aggressive behaviors in the hospital setting, with a special focus on the European experience. Recent Findings A number of variables, including individual, historical, and contextual variables, are significant risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 118 publications
(109 reference statements)
2
16
0
1
Order By: Relevance
“…Wu et al recently reported that 20.86% of physicians in general hospitals had encountered MD, which was much lower than our findings. 20 This gap may be due to the characteristics of the patients and their families, 33 the nature of psychiatric service, and the relative shortage of mental health resources. 34 There are several limitations about this study.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al recently reported that 20.86% of physicians in general hospitals had encountered MD, which was much lower than our findings. 20 This gap may be due to the characteristics of the patients and their families, 33 the nature of psychiatric service, and the relative shortage of mental health resources. 34 There are several limitations about this study.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses reported more positive attitudes toward patients who become aggressive or violent when they feel vulnerable, helpless, and afraid as measured by the ATABQ. Cognitive impairment, confusion, delirium, dementia, and alcohol and illegal drug intoxication or withdrawal are often detected in violent patients [ 1 , 20 , 21 , 79 , 80 ]. These illnesses and cognitive status limit patients’ ability to communicate effectively and understand the situation as the disease or discomfort progresses and its context during stay in ED.…”
Section: Discussionmentioning
confidence: 99%
“…Extant research indicated that internal risk factors encompassed clinical and personal factors. Other studies have identified alcohol intoxication, substance abuse, and mental illness as clinical factors for PVV among perpetrators [ 21 , 22 ]. Regarding personal factors or behavioral problems for PVV, male and younger patients/visitors, individual propensity to anger, hostile attributions, disease and discomfort, and low socioeconomic status are all possible factors [ 22 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have identified alcohol intoxication, substance abuse, and mental illness as clinical factors for PVV among perpetrators [ 21 , 22 ]. Regarding personal factors or behavioral problems for PVV, male and younger patients/visitors, individual propensity to anger, hostile attributions, disease and discomfort, and low socioeconomic status are all possible factors [ 22 , 25 ]. Environmental and process issues, and the sources of violence which constituted as external risk factors might simultaneously acted as triggers for violence in ED.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation